2007
DOI: 10.1002/jbm.a.31202
|View full text |Cite
|
Sign up to set email alerts
|

Biological roles of carboxymethyl‐chitin associated for the growth factor production

Abstract: Many techniques to restore cartilage defection have been tried. However, the development is still under way because of problems, including loosening of artificial joint, degenerative change of compensated tissue, risk of viral transmission via allograft/autograft, and cost of therapeutic materials for repair. In the previous research, we found that complementing cartilage defective part with carboxymethyl-chitin (CM-chitin)/beta-tricalcium phosphate composite induced regeneration of cartilage in rabbits in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…17 It is also accounted in cartilage restoration by induction of inflammatory cytokine and growth factors. 18 The intravascular resorbability of carboxymethyl chitin considers it efficient in terms of biological safety which is due to its hydrolysis to an oligomer during inflammation followed by its excretion as urea. [19][20][21][22][23][24][25] Our objective was based on a biomimetic approach, in which we prepared a series of 3D scaffolds including n-HA/ gel and n-HA/gel/CMC using the solvent-casting method combined with freeze-drying and compared them, so as to test the effect of CMC (prepared by chemical modification of chitin) on the developed construct.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is also accounted in cartilage restoration by induction of inflammatory cytokine and growth factors. 18 The intravascular resorbability of carboxymethyl chitin considers it efficient in terms of biological safety which is due to its hydrolysis to an oligomer during inflammation followed by its excretion as urea. [19][20][21][22][23][24][25] Our objective was based on a biomimetic approach, in which we prepared a series of 3D scaffolds including n-HA/ gel and n-HA/gel/CMC using the solvent-casting method combined with freeze-drying and compared them, so as to test the effect of CMC (prepared by chemical modification of chitin) on the developed construct.…”
Section: Introductionmentioning
confidence: 99%
“…The LDH values and cell numbers of each group were analyzed for statistical significance using Welch's t ‐test. Total RNA was extracted from the cells at 7, 14, and 21 days, and the mRNA expression of growth factors and cartilage‐related genes was analyzed using the reverse‐transcriptase polymerase chain reaction (RT‐PCR) as described previously 23. The pairs of primer sequences used were as follows: For β‐actin: 5′‐ATGGATGACGATATCGCT‐3′ (sense) and 5′‐ATGAGGTAGTCTGTCAGGT‐3′ (antisense).…”
Section: Methodsmentioning
confidence: 79%
“…We recently found that CM‐chitin stimulates immune cells to produce TGF‐β1, a growth factor for cartilage regeneration 23. However, it was unclear whether the stimulation of cells by CM‐chitin leads to cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation